Welfare Reform: Unresolved Issues - Mageean, Deirdre (Maine Policy Review, 1995)
As this issue goes to press, the U.S. Congress debates passage of sweeping legislative reforms to welfare, shifting responsibility to the states via block grants. In this Margaret Chase Smith Essay, Deirdre Mageean highlights several unresolved welfare reform issues.
Keywords: welfare reform